Aplicabilidade do custo-padrão com o auxílio do ERP no processo de planejamento e controle dos custos - Gutierrez, Vania Cristina Pastri (2009)
The Standard-Cost is an important indicator of the planning, execution, control and action on the company management, since it represents the cost established prior to the production, being based on previously planned conditions, with a main objective to establish a goal to be accomplished in the execution of the company s activities, and also to provide subsidies to the performance evaluation through the analysis of identified variations. In general, knowing and analyzing the variations between the values and standard measures with the real, implies on identifying its origins and motives, seeking to adopt necessary arrangements to eliminate or at least to reduce the possible deviations and inefficiency. Many companies are adopting the integrated ERP system, which is an information system that integrates all the data and process of an organization into one single system, software with the objective to assist the manager. In this manner, this paper presents a case study of a steel company located on a city in the interior of the state of São Paulo, that utilizes the integrated ERP system. It was analyzed the production of machines on the 101 line which has as a cost center lines 101 and 102, with the intention to identify the deviations between Standard-Cost and real and to verify if the Standard-Cost remains being useful on the expenditures control and management process on a company that uses the integrated ERP system. This paper presents in its specific objective the ERP as a facilitating tool of the standard-cost processing and establish a comparison between the Standard-Cost and the Real Cost, utilizing, for that goal, the method of exploratory research with a Unique Case Study. This paper is justified because it contributes to the scientific community when it opens paths to new suggestions, improvements and applications on this field. Over all, it is verified in the study that the Standard-cost remains being useful and it is reassured that the integrated ERP system as a facilitating tool of the standard-cost processing contributes to the identification of the variations and to the decision making in real time. It becomes evident on worksheets of an assembly lot that some components suffer variations of Efficiency and Price, of Volume, or both. Considering that the conclusions of a study case should not be generalized and that the results of this research were obtained from only one company, it is suggested to the future researchers that the theme of this research be fulfilled in companies of others sectors